The Long Run Impact of Childhood Interracial Contact on Residential Segregation - Luca Paolo Merlino; Max F. Steinhardt; Liam Wren-Lewis (Institute of Labor Economics (IZA), 2022)
This paper exploits quasi-random variation in the share of Black students across cohorts within US schools to investigate whether interracial contact in childhood impacts the residential choices of Whites in adulthood. We find that, 20 years after exposure, Whites who had more Black peers of the same gender in their grade go on to live in census tracts with more Black residents. Further investigation suggests that this result is unlikely to be driven by economic opportunities or social networks. Instead, the effect on residential choice appears to come from a change in preferences among Whites.
Keywords: I29; J15; R23; 330; residential segregation; social contact; race